Formative Research and Research Competencies in Foreign Language Students in Higher Education - Laura-De La Cruz, Kevin Mario; Pérez Yufra, Domingo Nicolás; Mendoza-Gómez , Cecilia Rosario del Pilar; Mendoza-Del Valle, Luz Anabella (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The purpose of this study was to ascertain the degree of correlation between formative research and the attainment of research competencies by students majoring in Foreign Language at a Peruvian public university. Using a non-probabilistic sampling method, 59 colleague students were selected for the sample. The design of the study was non-experimental and transactional in nature. The correlation coefficient between the variables was calculated to be 0.705, indicating that the relationship is positive and has a strong positive correlation. Consequently, there is a significant relationship between the variables of the study.